Mengkaji Konsep Desain Generatif Dalam Dunia Konstruksi Kontemporer Pada Bangunan Great Court Di London - Rustama Fasda Bimatukmaru; Ashadi Ashadi (Program Sarjana Arsitektur Universitas Internasional Batam, 2021)
The Great Court building is a contemporary-style building that is thought to have applied the generative concept to its construction. The purpose of this research is to understand the generative design concept in the contemporary construction world, to the characteristics and application of the Great Court building. Through qualitative methods and descriptive approaches in this study to gain knowledge of generative concepts in the world of contemporary construction, to case studies of the Great Court building. The Great Court building has the characteristics of a generative concept characteristic of building construction elements. The results of this study indicate that the generative concept of contemporary construction has several principles that exist in buildings, such as complex and complex shapes; a unified form; dynamic form; complex curved geometric shapes; and forms of repetition and symmetry.